2017
DOI: 10.1016/j.ajog.2016.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-intensity training on cardiovascular risk factors in premenopausal and postmenopausal women

Abstract: Cardiovascular risk factors are similar in late premenopausal and early postmenopausal women, matched by age and body composition, with the exception that postmenopausal women have higher high- and low-density lipoprotein-cholesterol levels. A 3-month intervention of high-intensity aerobic training reduces risk factors for type 2 diabetes and cardiovascular disease to a similar extent in late premenopausal and early postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
79
1
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(96 citation statements)
references
References 30 publications
7
79
1
9
Order By: Relevance
“…It is important to point out that BP data were previously reported on these groups of women and were found to be unaltered with training. 34 The reason for this discrepancy is likely that the number of included participants was lower in the present group and there was a slight difference in statistical approach.…”
Section: Participant Characteristicsmentioning
confidence: 75%
See 3 more Smart Citations
“…It is important to point out that BP data were previously reported on these groups of women and were found to be unaltered with training. 34 The reason for this discrepancy is likely that the number of included participants was lower in the present group and there was a slight difference in statistical approach.…”
Section: Participant Characteristicsmentioning
confidence: 75%
“…There was a decrease ( P= 0.0001) in resting HR after the training period in the postmenopausal group (5.2%), but the change in HR at rest in the premenopausal group did not reach statistical significance. Data on low‐density lipoprotein cholesterol, high‐density lipoprotein cholesterol, and triglycerides are presented elsewhere …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study investigated the research questions by using samples from two separate studies with the aim of investigating the effects of floorball and spinning, respectively, on participants' cardiovascular and musculoskeletal health; the details as well as the results of studies are reported elsewhere (Mandrup, et al, 2017;Nyberg, et al, 2014). The studies were approved by the Ethics Committee of Copenhagen and Frederiksberg communities Region H (H-1-2012-150) and conducted in accordance with the guidelines of the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%